Comparision of Propofol versus Combination of the Sevo?urane -Propofol for Inclusion of Laryngeal Mask Airway (LMA) Insertion of Adults - Kari Bala Krishna; Das, Pradeep Kumar; Hemnath Babu Kotla; Sri Harsha Merugu (Academia Anesthesiologica International, 2021)
Background: In the case of suspected injury, the most significant duty for an anaesthetist is to protect the airway with minimal cervical spine movement. The most significant cause of morbidity and mortality in these patients is an rise in the number of intubation attempts or the number of unsuccessful intubations. The aim of the studie is to compare the characteristics of insertion of LMA, and to calculate the extent of the respiratory problem and the cardiovascular problem between groups. Subjects and Methods: A proposed randomized research was organized on 60 patients grade of ASA Ist & IInd aged in between 18 - 60 years were randomized into two groups go through minor surgical measures under the normal anesthesia. Inj. Fentanyl 1ug/kg was given to both the Groups of sick person. Propofol 2 mg/kg was given in a Group of P. Group SP patients were induced with 8% sevoflurane in the 2:1 ratios of the nitrous oxide to O2 using vital capacity breathing technique with the Propofol 1 mg/kg. The characteristics of LA insertion, hemodynamics and extent of respiratory complications were assesses while inserting LMA. Results: There do no difference with groups along respects to the weight, sex, age, Patients in the Group SP get a lengthy time to losing of the eyelash responsive as of in comparison to the Patients in a Group of P. the time for the successful inclusion of the LMA was continued in Group of SP as in comparison with Group of P. All inclusions of LMA do victorious in the two groups. the period of the apnea has continued in the group of P as in comparison with the Group SP , & extent apnea has other frequent in a Group of P as in comparison with the Group SP. the total extent of problem associated to introduction of the anesthesia, were comparable with two groups. During inclusion of LMA, another patients carry movements in a Group of P. the extent of the vomiting (PONV) & postoperative nausea, Hence this was another frequent in a Group of SP as in comparison with the Group of the P. Conclusion : Sevoflurane is therefore an appropriate alternate to the propofol in adults for the LMA inclusion.